PENGARUH MODEL PEMBELAJARAN SOMATIC AUDITORY VISUALIZATION INTELLECTUAL (SAVI) DENGAN MEDIA FILM TERHADAP HASIL BELAJAR SEJARAH SISWA KELAS XI IPS MAN MODEL BANDA ACEH - Ayu Safarena; Mawardi .; Anwar Yoesoef (Universitas Syiah Kuala, 2018)
The learning process with the Somatic Auditory Visusalization (SAVI) learning model with film media is a learning activity that involves all senses with physical movements, seeing, hearing, and solving problems. The selection of film media can help SAVI learning models be more effective. The study entitled